2022
DOI: 10.1155/2022/5987582
|View full text |Cite|
|
Sign up to set email alerts
|

An Intervention Study on Children’s Healthy Joint Attention Skills Based on a Mixed Instructional Approach of DTT and PRT

Abstract: Joint attention is an important element that influences children’s early development of communication and sociality, and joint attention is more often than not the earliest incipient of their prosocial behavior. Joint attention skills are one of the core deficits of children with autism, and identifying and remediating the core problems of autism is a popular area of interest, with joint attention being the focus of attention. The aim of this study was to investigate whether the combined orientation model of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Children's pointing and concentrate on specific things are examples of children's psychological activity, and these actions are referred to as children's concentration [1,2]. Children's mental activity are said to be direct when they point away from one thing at a specific point and toward other objects, a sign of their selectivity [3][4][5][6]. Although it cannot be compared to a child's IQ, a child's intelligence will be somewhat impacted by their level of concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Children's pointing and concentrate on specific things are examples of children's psychological activity, and these actions are referred to as children's concentration [1,2]. Children's mental activity are said to be direct when they point away from one thing at a specific point and toward other objects, a sign of their selectivity [3][4][5][6]. Although it cannot be compared to a child's IQ, a child's intelligence will be somewhat impacted by their level of concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%